2012
DOI: 10.1111/j.1610-0387.2012.08003.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of anticoagulation during dermatosurgical procedures in Germany – results from a cross‐sectional study

Abstract: Large differences in the perioperative management of anticoagulant therapy during dermatosurgical procedures have been identified. Further studies and guidelines should be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 15 publications
0
19
0
10
Order By: Relevance
“…The perioperative management of patients taking anticoagulation therapy is a challenge for all surgical specialties, and physicians are confronted with the decision of whether to continue or discontinue drugs …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The perioperative management of patients taking anticoagulation therapy is a challenge for all surgical specialties, and physicians are confronted with the decision of whether to continue or discontinue drugs …”
Section: Introductionmentioning
confidence: 99%
“…The perioperative management of patients taking anticoagulation therapy is a challenge for all surgical specialties, and physicians are confronted with the decision of whether to continue or discontinue drugs. [1][2][3][4][5][6][7] The standard anticoagulation therapy after placement of coronary artery stents is clopidogrel and acetylsalicylic acid (ASA), which is also used for patients with unstable angina or after a non-ST-segment elevation myocardial infarction. [8][9][10] Phenprocoumon or warfarin is often used after thrombosis or pulmonary embolism and may be combined with ASA for patients with mechanical heart valves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perioperative management of these medications remains a challenge for most dermatologists. In dermatology but also in other disciplines, health care research has shown large heterogeneity in the perioperative management of anticoagulation . In a cross‐sectional study in Germany, 40% of the dermatologists working in dermatosurgery in hospitals would recommend stopping low‐dose (<100 mg) aspirin prior to large excision, whereas 54% would recommend to continue the treatment (no answer 6.2%).…”
Section: Introductionmentioning
confidence: 99%
“…Actualmente, y como norma general, no está justificada la retirada de estos fá rmacos durante una cirugía dermatoló gica convencional, salvo petició n expresa de otro especialista 11 .…”
Section: Hemorragiaunclassified